RISK ASSESSMENT ON THE DECOMMISSIONING STAGE OF INDONESIAN TRIGA 2000 RESEARCH REACTOR - Ratih Luhuring Tyas; Deswandri Deswandri; Dinnia Intaningrum; Julwan Hendry Purba (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2022)
Decommissioning is the final stage of a nuclear reactor. In preparing the decommissioning plan, one of the important elements that need to be considered is safety assessment. During decommissioning, there are many complex tasks to be done where the radiological and non-radiological hazards arise and can significantly affect not only the workers but also the general public and the environment. Indonesia has no experience with nuclear reactor decommissioning, so it is necessary to study various experiences of decommissioning activities in the world. This study proposes a framework to implement the safety assessment on the decommissioning of the TRIGA 2000 research reactor. The framework was developed on desk-based research and analysis. The proposed framework involves the facility and decommissioning activities, hazard identification, hazard analysis, hazard evaluation, hazard or risk control, and independent review.